Aquaglyceroporins Are Differentially Expressed in Beige and White Adipocytes - da Silva, Inês Vieira; Díaz-Sáez, Francisco; Zorzano, António; Gumà, Anna; Camps, Marta; Soveral, Graça (International journal of molecular sciences, 2020)
Browning of white adipocytes has been proposed as a powerful strategy to overcome metabolic complications, since brown adipocytes are more catabolic, expending energy as a heat form. However, the biological pathways involved in the browning process are still unclear. Aquaglyceroporins are a sub-class of aquaporin water channels that also permeate glycerol and are involved in body energy homeostasis. In the adipose tissue, aquaporin-7 (AQP7) is the most representative isoform, being crucial for white adipocyte fully differentiation and glycerol metabolism. The altered expression of AQP7 is involved in the onset of obesity and metabolic disorders. Herein, we investigated if aquaglyceroporins are implicated in beige adipocyte differentiation, similar to white cells. Thus, we optimized a protocol of murine 3T3-L1 preadipocytes browning that displayed increased beige and decreased white adipose tissue features at both gene and protein levels and evaluated aquaporin expression patterns along the differentiation process together with cellular lipid content. Our results revealed that AQP7 and aquaporin-9 (AQP9) expression was downregulated throughout beige adipocyte differentiation compared to white differentiation, which may be related to the beige physiological role of heat production from oxidative metabolism, contrasting with the anabolic/catabolic lipid metabolism requiring glycerol gateways occurring in white adipose cells.